Eksistensi Doding Pada Kalangan Muda Simalungun - Sapna Sitopu; Rahmatika Luthfiana Sholikhah; Rithaony Hutajulu (Universitas Negeri Medan, 2025)
This research aims to describe the existence of Simalungun doding performed with inggou among the younger generation of Simalungun and analyze the factors that influence the continuity of this tradition. Using a qualitative approach, this research examines how Wallace & Srb's adaptation theory can explain the phenomenon. The results show that doding with inggou, as an integral part of Simalungun culture, has an important role in maintaining the identity and social values of the community. However, the existence of this tradition among the younger generation is increasingly diminishing due to the influence of modernization and globalization. The lack of understanding of the values contained in doding and the lack of conservation efforts are the main factors that cause this. This research concludes that strategic efforts are needed to revive the doding tradition with inggou among the younger generation, such as through education, socialization, and innovations that are relevant to the times.